Vitamin D deficiency in pregnancy and the risk of preterm birth: a nested case-control study - Tashnia Tahsin; Rasheda Khanam; Nabidul Haque Chowdhury; A. S. M. Tarik Hasan; Md. Biplob Hosen; Sayedur Rahman; Anjan Kumar Roy; Salahuddin Ahmed; Rubhana Raqib; Abdullah H. Baqui (BMC, 2023)
Abstract Background Each year, an estimated 15 million babies are born preterm. Micronutrient deficiencies, including vitamin D deficiency (VDD), are common in many low- and middle-income countries (LMICs), and these conditions are often associated with adverse pregnancy outcomes. Bangladesh experiences a high prevalence of VDD. The country also has a high preterm birth (PTB) rate. Using data from a population-based pregnancy cohort, we estimated the burden of VDD during pregnancy and its association with PTB. Methods Pregnant women (N = 3,000) were enrolled after ultrasound confirmation of gestational age at 8-19 weeks of gestation. Trained health workers prospectively collected phenotypic and epidemiological data at scheduled home visits. Trained phlebotomists collected maternal blood samples at enrollment and 24 -28 weeks of gestation. Aliquots of serum were stored at -800 C. We conducted a nested case-control study with all PTB (n = 262) and a random sample of term births (n = 668). The outcome, PTB, was defined as live births < 37 weeks of gestation, based on ultrasound. The main exposure was vitamin D concentrations of 24-28 weeks maternal blood samples. The analysis was adjusted for other PTB risk factors. Women were categorized as VDD (lowest quartile of 25(OH)D; <  = 30.25 nmol/L) or not deficient (upper-three quartiles of 25(OH)D; > 30.25 nmol/L). We used logistic regression to determine the association of VDD with PTB, adjusting for potential confounders. Results The median and interquartile range of serum 25(OH)D was 38.0 nmol/L; 30.18 to 48.52 (nmol/L). After adjusting for co-variates, VDD was significantly associated with PTB [adjusted odds ratio (aOR) = 1.53, 95% confidence interval (CI) = 1.10 - 2.12]. The risk of PTB was also higher among women who were shorter (aOR = 1.81, 95% CI: 1.27-2.57), primiparous (aOR = 1.55, 95% CI = 1.12 - 2.12), passive smokers (aOR = 1.60, 95% CI = 1.09 - 2.34), and those who received iron supplementation during pregnancy (aOR = 1.66, 95% CI: 1.17, 2.37). Conclusion VDD is common in Bangladeshi pregnant women and is associated with an increased risk of PTB.